Light music - Muhammad Noor, Ahmad Shukri; Zan, Zuraidah; Yaakob, Syamsuri; Mohd Ali, Azizi (Universiti Putra Malaysia Press, 2017)
Our universe is full of light. Light can be both obvious and mysterious. Some can be seen with our naked eye and some are not. Through its special properties, light wave is used to connect the globe by carrying messages and information, with its superior speed and vast bandwidth.